Phenylephrine for Blood Pressure Control under Sub-arachnoid Block in Elective Caesarean Section: Prophylactic vs Therapeutic Approach - Thakur, Anand; Bhattarai, Amit Sharma; Acharya, Binita (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: Hypotension after spinal anaesthesia is common during Caesarean section with incidence of 50 - 80%. There are various methods to prevent maternal side effects like hypotension, nausea and vomiting and fetal outcome by preloading or co-loading with crystalloids, left tilt and vasopressors like phenylephrine. In this study we hypothesized that prophylactic phenylephrine offers better hemodynamic control than therapeutic doses in elective Caesarean section after subarachnoid block. Methods: A comparative, prospective, randomized double blind study was conducted in 104 patients scheduled for elective Caesarean section. 52 patients each were assigned into either prophylactic (P) or therapeutic (T) group. Baseline data, hemodynamics, nausea and vomiting and APGAR score were collected. Hemodynamics were analyzed using 2-tailed student’s t-test for intergroup and paired t-test for intragroup comparison. Nominal categorical data such as gender was also analyzed with Chi-square test. Results: Systolic, diastolic and mean arterial pressure were significantly lower in therapeutic group as compared to prophylactic group. The overall incidence of hypotension was 53% in group T and 21% in group P. Similarly, nausea and vomiting were significantly higher in group T (46%) compared to group P (11%) at 15, 20 and 30 mins. Conclusion: Prophylactic dose of phenylephrine significantly prevents hypotension and nausea and vomiting in patients undergoing elective Caesarean section.